Identifikasi Jenis dan Kepadatan Mikroplastik pada Sedimen Mangrove di Kawasan Estuari Perancak Kabupaten Jembrana, Bali - Apryawan, Gede Eko; Hendrawan, I Gede; Widiastuti, Widiastuti (Journal of Marine Research and Technology, 2024)
Waste is a problem for communities all over the world. Microplastics are found in the environment, mangrove beach sediments, and worldwide oceans. Microplastics are plastic particles measuring <5 mm. The Perancak mangrove forest area, Jembrana Regency, Bali, is an estuary area with complex activities, namely tourism, fishing, and residential. This research aimed to determine the type and density of microplastics in mangrove sediments using cluster analysis of residential areas in large and small rivers. The method used is simple random sampling with 10 points in each cluster. The sampling method uses a pipe with a diameter of 7.5 cm, a depth of 20 cm. Sediment sample processing used the Masura method, 2015, and density calculations used the NOAA 2013 formula. The number of microplastics found was 517 particles. Population clusters had 101 particles, large rivers had 103 particles, and small rivers had 313 particles. The types of microplastics found were 213 particles in film, 28 particles in fragments, 46 particles in fiber, and 230 particles in foam. Microplastic density calculations yielded 30.21 particles/kg in the Residential Cluster, 34.11 particles/kg in the large river Cluster, and 95.07 particles/kg in the small river Cluster. Model testing using the GAM Generalized Additive Models model) with the lowest AIC value shows that small river and residential clusters significantly influence microplastic particles. In contrast, large river clusters are not significant. There is no significant effect on the number of microplastic particles at residential points and tourist points because the rice field points significantly influence the number of microplastic particles.